Factors associated with short sleep duration in adolescents - Érico Pereira Gomes Felden; Douglas Filipin; Diego Grasel Barbosa; Rubian Diego Andrade; Carolina Meyer; Fernando Mazilli Louzada (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: This study aimed to investigate the prevalence and factors associated with short sleep duration in adolescents from Maravilha - Santa Catarina (SC), southern Brazil. Methods: The sample consisted of 516 adolescents aged 10-19 years of both genders. Issues associated with short sleep duration and difficulty falling asleep, chronotype, daytime sleepiness, physical activity, sedentary behavior and weight status were investigated. Results: The prevalence of short sleep duration (<8h on school days) was 53.6%. Adolescents aged 17-19 years showed a 2.05-fold (95%CI: 1.20-3.50) greater prevalence of short sleep duration than those aged 10-12 years. The ones studying in morning and evening shifts had a higher prevalence of short sleep duration compared to those in the afternoon shift. Older age and school shift were the main factors associated with short sleep duration. Conclusions: Adolescents from Maravilha showed high prevalence of short sleep duration, and older adolescents that studied in the morning and evening shifts showed reduced sleep.